Analisis Kinerja Keuangan terhadap Nilai Perusahaan dengan Corporate Social Responsibility sebagai Variabel Moderasi - Dyah Aruning Puspita; Adrian Christianto (Bulletin of Management and Business, 2021)
The increased company value will be a long-term goal of a company. By providing an overview of the social responsibility of the community through the Corporate Social Responsibility (CSR) program to maximize the profitability and solvency of financial performance, the company's value can be increased. The objectives of this study are to: 1) determine whether profitability affects the value of transportation companies that have been listed on the IDX in 2016-2018. 2) determine whether Solvency affects the value of transportation companies listed on the IDX in 2016-2018. 3) To find out whether CSR disclosure moderates the relationship between profitability and company value in transportation companies that have been listed on the IDX in 2016-2018. 4) To find out whether CSR disclosure moderates the relationship between company solvency and company value in transportation companies that have been listed on the IDX in 2016-2018. The results showed that profitability had a significant negative effect on firm value. Meanwhile, solvency has a significant positive effect on firm value. Meanwhile, CSR disclosure cannot moderate the relationship between profitability and firm value. CSR disclosure cannot moderate the relationship between solvency and firm value.